2015
DOI: 10.1111/and.12437
|View full text |Cite
|
Sign up to set email alerts
|

Changes in erectile organ structure and function in a rat model of chronic prostatitis/chronic pelvic pain syndrome

Abstract: There is a growing recognition of the association between chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and erectile dysfunction (ED); however, most of the reports are based on questionnaires which cannot distinguish between organic and functional ED. The purpose of this study was to determine the exact relationship between CP/CPPS and ED, and to investigate the changes in erectile organ structure and function in a rat model of CP/CPPS. We established a rat model of experimental autoimmune prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
(39 reference statements)
3
7
0
1
Order By: Relevance
“…EAP is induced by multipoint subcutaneous injection of prostate antigen with an adjuvant, leading to T‐cell activation and inflammatory cell infiltration of the prostate gland (Kurita, Yamaguchi, Okamoto, Kotera, & Oka, ). The pathological changes of the prostate tissue in EAP rats shown in this study are consistent with that demonstrated in previous studies (Wang et al, ; Wang et al, ). The prostate glands in the EAP group presented with inhomogeneous tissue hyperplasia, and the basal lamina was partially destroyed, accompanied by chronic inflammatory cell infiltration, whereas the glandular epithelial structure of the control group was intact without tissue oedema or inflammatory cell infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…EAP is induced by multipoint subcutaneous injection of prostate antigen with an adjuvant, leading to T‐cell activation and inflammatory cell infiltration of the prostate gland (Kurita, Yamaguchi, Okamoto, Kotera, & Oka, ). The pathological changes of the prostate tissue in EAP rats shown in this study are consistent with that demonstrated in previous studies (Wang et al, ; Wang et al, ). The prostate glands in the EAP group presented with inhomogeneous tissue hyperplasia, and the basal lamina was partially destroyed, accompanied by chronic inflammatory cell infiltration, whereas the glandular epithelial structure of the control group was intact without tissue oedema or inflammatory cell infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…While in rats of control group, the glandular epithelium structure of prostate glands was integrated and clear without inflammatory cells infiltration and tissue hyperplasia. The histopathological features of prostate tissues in our study conformed to the diagnosis criteria about the rat model of experimental prostatitis that mimic the human CP/CPPS (Wang et al ., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of CP⁄CPPS remains poorly understood, but accumulating evidence supports that autoimmune factors have become a predominant component (Zhang et al ., ). A rat model of experimental autoimmune prostatitis (EAP) is considered as a suitable model for human CP⁄CPPS, which is based on a previously described method (Motrich et al ., ; Wang et al ., ,b). EAP rat is characterized by a prostate‐specific autoimmune response associated with the infiltration of inflammatory cells and shares many clinical, pathological features with human CP⁄CPPS (Vykhovanets et al ., ; Penna et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…CP/CPPS is a common disease in human males. Its chronic pelvic pain not only affects the quality of life and emotional state of the patients, but also decreases the quality of their semen, resulting in subfertility . The penile erection function in CP/CPPS patients might also be reduced .…”
Section: Discussionmentioning
confidence: 99%